Selfhood and the soul : essays on ancient thought and literature in honour of Christopher Gill - Seaford, Richard; Seaford, Richard; Wilkins, John; Wilkins, John; Wright, Matthew; Wright, Matthew (Oxford University Press, 2017)
'Selfhood and the Soul' is a collection of original essays in honour of Christopher Gill, Emeritus Professor of Ancient Thought at the University of Exeter. The contributions cover a wide range of approaches and topics, but all are committed to examining central issues about the experience of being a person and the question of how best to live